Translating Turkish Foreign Policy from English into Turkish - Okyayuz Yener, Şirin (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
When translating politics the translator considers the intention of the author, his style and discourse, and the information given, but s/he also considers that the sensitivity to politics and how the political discourse is built differ from culture to culture. The following paper is an attempt to identify some of the problems that may be encountered when translating politics in Turkey in the light of these considerations and through examples from a translation to suggest strategies to overcome these difficulties, considering the outcomes of alternative strategies that could be employed. It is a chronicle of the translator’s attempt to exemplify how to remain faithful to many at the same time: the author, the meaning, the intention, the norms of the publishers, the TL readers and the two diverse political cultures.